Genome-wide comparative analysis of photosynthetic enzymatic genes provides novel insights into foxtail millet and other cereals - Raturi, Arpit; Shekhar, Shivam; Jha, Ratnesh Kumar; Chauhan, Divya; Pandey, Saurabh; Kumari, Sarita; Singh, Ashutosh (Frontiers in Genetics, 2024)
Due to more efficient photosynthetic pathways present in C4 crops have higher photosynthetic capacity and nitrogen and water use efficiency than C3 crops. Previous research has demonstrated that the genomes of C3 species include and express every gene needed for the C4 photosynthesis pathway. However very little is known about the dynamics and evolutionary history of these genes' evolution in C4 plants. In this study gene encoding five key photosynthetic pathway enzymes (PEPC, ME-NADP, MDH, RbcS, and PPDK) in the genome C3 (rice), C4 (maize, sorghum and foxtail millets) and CAM (Pineapple) were identified and systematically compared. The number of genes of these photosynthetic enzymes were highest in C4 crops such as sorghum and foxtail millets while only 8 genes were identified in CAM plants. However, 16 genes were identified in rice (C3 crop). Further, physical, chemical, gene structure and, cis-element analysis were performed to study the complete insight of these key genes. Tissue-specific expression showed that the most of photosynthetic genes are expressed in leave tissue. Comparisons of expression characteristics confirmed that the expression patterns of non-photosynthetic gene copies were relatively conserved among species, while C4 gene copies in C4 species acquired new tissue expression patterns during evolution.Additionally, multiple sequence features that may affect C4 gene expression and subcellular localization were found in the coding and promoter regions. Our research also highlighted the variety in how different genes have evolved within the C4 photosynthetic pathway, and it was confirmed that the specific high expression in leaves and the right distribution within cells were crucial for the development of C4 photosynthesis. The findings from this study will aid in understanding the evolutionary process of the C4 photosynthetic pathway in grasses and offer insights for modifying C4 photosynthetic pathways in wheat, rice, and other significant C3 cereal crops.